Using Health Check Data to Understand Risks for Dementia and Cognitive Impairment Among Torres Strait Islander and Aboriginal Peoples in Northern Queensland—A Data Linkage Study - Thompson, Fintan; Russell, Sarah G.; Harriss, Linton R.; Esterman, Adrian; Taylor, Sean; Quigley, Rachel; Strivens, Edward; McDermott, Robyn (Frontiers in Public Health, 2022)
Objective: High rates of dementia are evident in First Nations populations, and modifiable risk factors may be contributing to this increased risk. This study aimed to use a longitudinal dataset to gain insights into the long-term risk and protective factors for dementia and cognitive impairment not dementia (CIND) in a Torres Strait Islander and Aboriginal population in Far North Queensland, Australia. Study Design and Setting: Probabilistic data linkage was used to combine baseline health check data obtained in 1998/2000 and 2006/2007 for 64 residents in remote communities with their results on a single dementia assessment 10-20 years later (2015-2018). The relationship between earlier measures and later CIND/dementia status was examined using generalised linear modelling with risk ratios (RRs). Due to the small sample size, bootstrapping was used to inform variable selection during multivariable modelling. Results: One third of participants (n=21, 32.8%) were diagnosed with dementia (n=6) or CIND (n=15) at follow-up. Secondary school or further education (RR=0.38, 95%CI 0.19-0.76, p=0.006) and adequate levels of self-reported physical activity (RR=0.26, 95%CI 0.13-0.52, p<0.001) were repeatedly selected in bootstrapping and showed some evidence of protection against later CIND/dementia in final multivariate models, although these had moderate collinearity. Vascular risk measures showed inconclusive or unexpected associations with later CIND/dementia risk. Conclusions: The preliminary findings from this small study highlighted two potential protective factors for dementia that may be present in this population. A tentative risk profile for later CIND/dementia risk is suggested, although the small sample size limits the applicability of these findings.